Airway inflammation in elite swimmers - Piacentini, G. L.; Rigotti, E.; Bodini, A.; Peroni, D.; Boner, A. L. (Journal of Allergy and Clinical Immunology, 2007)
Carraro et al1 recently demonstrated that exhaled nitric oxide (NO) was not increased in children attending indoor swimming pools for 1 to 2 hours a week. However, the same group has reported that an accidental acute chlorine exposure in a swimming pool can induce neutrophilic airway inflammation with increased leukotriene (LT) B4 levels in exhaled breath condensate (EBC), persisting for months.2 Furthermore, the chlorination of water in swimming pools has been demonstrated potentially to have detrimental effects on health of swimmers and swimming pool workers.3 On the basis of these reports, we performed a pilot investigation to explore the rationale for a wider study to assess the potential risk from the exposure to chlorinate compounds in swimming pools.